Coated Latex Beads as Artificial Cells for Quantitative Investigations of Receptor/Ligand Interactions. (4th November 2020) - Urlaub, Doris; Watzl, Carsten
Abstract: Cellular interactions are often essential to regulate immune cell activities during an immune response. To understand the details of this process, it is necessary to study individual receptor/ligand interactions in a quantitative fashion. However, this is often very difficult or even impossible when using real cells for stimulation. Here, we present a method to use cell‐sized latex beads for such studies. These beads can be coated with agonistic antibodies or specific ligands in a defined and quantifiable fashion. This creates the possibility of titrating the strength of the stimulation for a specific receptor in a three‐dimensional system. Using natural killer (NK) cells as an example, we demonstrate how these beads can be used to stimulate NK cell responses. © 2020 The Authors. Basic Protocol 1 : Covalent coating of latex beads with antibodies Basic Protocol 2 : Quantification of the amount of antibodies on the beads with the QIFIKIT ® Alternate Protocol 1 : Covalent coating of latex beads with streptavidin to bind biotinylated proteins Alternate Protocol 2 : Quantification of the amount of protein on the beads with the QIFIKIT ® Support Protocol : Functional testing of the beads in a natural killer cell degranulation assay